Septin roles in tumorigenesis - Diana Connolly; Inès Abdesselam; Pascal Verdier‐Pinard; Cristina Montagna (2011)
Abstract Septins are a family of cytoskeleton related proteins consisting of 14 members that associate and interact with actin and tubulin. From yeast to humans, septins maintain a conserved role in cytokinesis and they are also involved in a variety of other cellular functions including chromosome segregation, DNA repair, migration and apoptosis. Tumorigenesis entails major alterations in these processes. A substantial body of literature reveals that septins are overexpressed, downregulated or generate chimeric proteins with MLL in a plethora of solid tumors and in hematological malignancies. Thus, members of this gene family are emerging as key players in tumorigenesis. The analysis of septins during cancer initiation and progression is challenged by the presence of many family members and by their potential to produce numerous isoforms. However, the development and application of advanced technologies is allowing for a more detailed analysis of septins during tumorigenesis. Specifically, such applications have led to the establishment and validation of SEPT9 as a biomarker for the early detection of colorectal cancer. This review summarizes the current knowledge on the role of septins in tumorigenesis, emphasizing their significance and supporting their use as potential biomarkers in various cancer types.